The Bounty of Buffers: Spatial Measurement of Displacement and Diffusion of Benefits of Alarms on Burglary - Lee, Seungmug (Zech) (Crime & delinquency, 2024)
This study analyzes the extent to which alarm systems impact geographical displacement and/or diffusion of benefits on burglary, which regards as a substitute for the absence of capable guardians. A quasi-experimental design with three nested concentric zones—target, buffer, and control—are utilized by incorporating the WDQ conceptual approach with GIS and a parcel map. The datasets include burglary incidents and alarm permit records. Alarms produce a sizeable impact on burglary reduction. No indication of spatial displacement is observed from protected houses to nearby houses. Alarms create a short geographic ambit and a wider spatial range of diffusion of benefits. A burglar alarm can protect the house without displacing burglary to nearby houses and provides neighboring houses with protection as well.